Functionality, Selectivity, and Psychometric Characteristics of Items Used on Entrance Exam for Students with Special Abilities for Computer Sciencе - Dragana D. Stanojević; Elizabeta. M. Karalić; Branislav M. Ranđelović (University of Belgrade, Teacher Education Faculty, 2021)
The subject of this research is the quality of items on the entrance exam for students with special abilities for informatics and computer science. The aim of the research is to determine the quality of the items and the whole test, based on metric characteristics (reliability, informativity, discrimination, and difficulty of items). There was a total of 1926 participants in the sample of this research, while descriptive statistics and the item response theory (IRT) were used in the analysis. The conclusions of this research will be useful for improving the quality of the items on the entrance exam for students with special abilities for informatics and computer science, and will therefore enable the successful selection of candidates for education in one of the most promising and attractive sectors today, the sector of information technologies.